Influence of barrier layer indium on efficiency and wavelength of InGaN multiple quantum well (MQW) with and without semi‐bulk InGaN buffer for blue to green regime emission. Issue 8 (9th March 2017) - Alam, Saiful; Sundaram, Suresh; li, Xin; Jamroz, Miryam E.; El Gmili, Youssef; Robin, Ivan C.; Voss, Paul L.; Salvestrini, Jean‐Paul; Ougazzaden, Abdallah
Abstract : The effect of indium (In) in the barrier of InGaN/GaN multiple quantum well (MQW) has been studied for MQWs with and without semi‐bulk InGaN buffer. From simulation, the optimum In content in the barrier with 3–5 nm width is 5–7% to get the optimal material quality and internal quantum efficiency (IQE) of ∼65% for 450–480 nm emission range. Simulation shows a reduction of the potential barrier due to band flattening, a more homogeneous distribution of electrons and holes in the active region and subsequently, a more radiative recombination rate with InGaN as barrier layer. Both cathodoluminescence (CL) and photoluminescence (PL) experimental results show a blue‐shift of emission wavelength along with an enhancement in the emission intensity when GaN barrier is replaced with InGaN barrier, for a MQW structure both with and without the semi‐bulk InGaN buffer. We attribute this blue shift to the reduced polarization mismatch and increased effective bandgap. This InGaN barrier‐related improvement in IQE and efficiency droop could be useful for the realization of longer wavelength "green‐gap" range LEDs where poor IQE and efficiency droop are more prominent due to high indium (In) in the active region.